Evaluasi Efektivitas Kunjungan Rawat Jalan dengan Menggunakan Alur Pendaftaran E-Registrasi di RS Bhayangkara TK III Palangkaraya Tahun 2025 - Nur Aini, Uliza; Rumengan, Grace; Satria, Budi (Dinasti Research, 2025)
The development of information and communication technology has driven innovations in healthcare services, one of which is E-Registration, aimed at improving administrative efficiency and enhancing patient experiences during outpatient registration. This study was conducted at Bhayangkara Hospital Level III Palangka Raya, which has implemented the SIAP Online V2 application as its e-registration system. The research design used was quantitative with a cross-sectional approach. The independent variables in this study were the use of e-registration flow and patient satisfaction, while the dependent variable was service effectiveness. The main analytical instruments employed were univariate, bivariate, and multivariate analyses, with data processed using SPSS version 25. The results showed that outpatient visits between May and July 2025 indicated an increase in e-registration usage from 83% in May to 90% in July. Statistical analysis revealed that the registration flow did not significantly affect outpatient service effectiveness (p = 0.154 > 0.05). Patient satisfaction was not found to have a direct influence on effectiveness, suggesting that service effectiveness is more determined by the smoothness of the registration flow rather than subjective perceptions of satisfaction. These findings confirm that e-registration plays an essential role in enhancing outpatient service effectiveness, while patient satisfaction serves more as a perceptual aspect that does not necessarily correlate with system efficiency.